L.S. Vygotsky on Giftedness as “A Higher Order Formation” - Fedorova, E.P. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2024)
The author explores the concept of giftedness as presented in the published scientific manuscripts of L.S. Vygotsky and in the newly released psychological dictionary co-authored by him. This article emphasizes the importance of utilizing these archival sources for contemporary research on the issue of giftedness. Through a theoretical analysis, it highlights key ideas regarding the understanding of giftedness from the perspective of cultural-historical psychology: the necessity of distinguishing between individual psychological functions and giftedness; the notion of giftedness as a "formation of the higher order", not reducible to the level of a separate function; the systems approach to studying giftedness; the role of the concept of development in elucidating the phenomenon of giftedness. The article also demonstrates the potential of L.S. Vygotsky for advancing research on research and enhancing practices Рассматривается представление об одаренности в опубликованных научных рукописях Л.С. Выготского и во вновь изданном первом психологическом словаре, соавтором которого он являлся. Автор обосновывает актуальность обращения к открывшимся архивным источникам для современных исследований проблемы одаренности. В ходе теоретического анализа выделены ключевые идеи в понимании одаренности с позиции культурно-исторической психологии: необходимость различения отдельных психологических функций и одаренности; понимание одаренности как «образования высшего порядка», не сводимого к высоте отдельной функции; системный подход к исследованию одаренности, роль понятия развития и значение социальной ситуации развития для раскрытия феномена одаренности. Демонстрируется потенциал идей Л.С. Выготского для исследований одаренности и образовательной практики.